2017
DOI: 10.1108/jcre-11-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Workplace productivity and office type

Abstract: Open plan office environments are considered to offer workplace productivity benefits because of the opportunities that they create for interaction and knowledge exchange, but more recent research has highlighted noise, distraction and loss of privacy as significant productivity penalties with this office layout. This study aims to investigate if the purported productivity benefits of open plan outweigh the potential productivity penalties. Design/methodology/approach Previous research suggests that office env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 73 publications
1
46
1
1
Order By: Relevance
“…The second highest score difference when compared to the entire dataset was found for "Connection to the outdoor environment" (1.21, Table 4), which includes questionnaire items access to daylight, external view, and connection to the outdoors (Table 1). This finding supports the significance of innovative design [28,32], communication and collaboration [26,59], and aesthetics [60] on office worker's satisfaction. With respect to occupants' satisfaction, the study showed significant relationships with access to daylight and view as indicated in other similar studies [45][46][47].…”
Section: Occupants' Satisfactionsupporting
confidence: 74%
See 2 more Smart Citations
“…The second highest score difference when compared to the entire dataset was found for "Connection to the outdoor environment" (1.21, Table 4), which includes questionnaire items access to daylight, external view, and connection to the outdoors (Table 1). This finding supports the significance of innovative design [28,32], communication and collaboration [26,59], and aesthetics [60] on office worker's satisfaction. With respect to occupants' satisfaction, the study showed significant relationships with access to daylight and view as indicated in other similar studies [45][46][47].…”
Section: Occupants' Satisfactionsupporting
confidence: 74%
“…• Visual comfort, access to daylight, and view [19][20][21]; • Noise distraction, lack of privacy, and communication [22][23][24][25][26][27]; • Office design [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from an early 20 th century study demonstrated that, although not working together, just being co-located in the same workspace increased the mental processes of association and thought [17], highlighting some benefits of being with others while working alone. A recent study by Haynes et al [18] also showed that social interactions and work interactions had positive associations with perceived impact on productivity. On the flip-side of this, the perceived ability to concentrate well depends on other environmental factors, with high noise levels and other distractions shown to have negative effects [19].…”
Section: Discussionmentioning
confidence: 91%
“…There is ongoing debate on the type of office environment that is not only comfortable for occupants but supports and enhances productivity [1][2][3]. At the centre of the debate is the comfort of occupants in office environments [4].…”
Section: Introductionmentioning
confidence: 99%